Effects of cadmium and high-fat diet on essential metal concentration in the mouse testis. (2021) - Zhou, Bin; Gentry, Adrienne; Xu, Qian; Young, Jamie L.; Yan, Xiaofang; Pagidas, Kelly; Yang, Yu; Watson, Walter H.; Kong, Maiying; Cai, Lu; Freedman, Jonathan H.
Graphical abstract: Highlights: Whole life exposure to low doses of cadmium results in a significant accumulation of metals in the testis. Co-exposure to cadmium with a high fat diet increases cadmium levels. Cadmium and high fat diet disrupt essential metal homeostasis in the testis. Abstract: The effects of exposure to the environmental toxicant cadmium, in combination with obesity, on the metal content in mouse testis were evaluated. Starting in utero and continuing through to 10 or 24 weeks post-weaning, male mice were exposed to cadmium (0, 0.5 or 5 ppm), and fed either a low (LFD) or high fat diet (HFD) post-weaning. Testicular levels of cadmium and essential metals were determined 10 and 24 weeks post-weaning by ICP-MS. Similar to what has been previously observed in the liver, kidney, heart and brain, significant levels of cadmium accumulated in the testis under all exposure conditions. Additionally, HFD-fed animals accumulated more cadmium than did their LFD-treated counterparts. Both treatments affected essential metal homeostasis in the testis. These findings suggest that cadmium and obesity may compromise the reproductive potential in the male mouse by disrupting essential metal levels.